2019
DOI: 10.1108/hff-02-2019-0150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic field on micro cross jet injection of dispersed nanoparticles in a microchannel

Abstract: Purpose Water/Al2O3 nanofluid with volume fractions of 0, 0.3 and 0.06 was investigated inside a rectangular microchannel. Jet injection of nanofluid was used to enhance the heat transfer under a homogeneous magnetic field with the strengths of Ha = 0, 20 and 40. Both slip velocity and no-slip boundary conditions were used. Design/methodology/approach The laminar flow was studied using Reynolds numbers of 1, 10 and 50. The results showed that in creep motion state, the constricted cross section caused by flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(29 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…Hayat et al [31] adumbrated the heat transfer of Newtonian fluids over an inclined stretching cylinder. Bagherzadeh et al [32] experimentally verified the enhancement in heat transfer rate by jet injection of a nanofluid under a homogeneous magnetic field. Goshayeshi et al [33] elaborated the effect of a ferro nanofluid on the enhancement of the thermal features of a flowing fluid within the heat pipe under the implication of a magnetic field.…”
Section: Literature Surveymentioning
confidence: 99%
“…Hayat et al [31] adumbrated the heat transfer of Newtonian fluids over an inclined stretching cylinder. Bagherzadeh et al [32] experimentally verified the enhancement in heat transfer rate by jet injection of a nanofluid under a homogeneous magnetic field. Goshayeshi et al [33] elaborated the effect of a ferro nanofluid on the enhancement of the thermal features of a flowing fluid within the heat pipe under the implication of a magnetic field.…”
Section: Literature Surveymentioning
confidence: 99%
“…In general, heat transfer techniques can be divided into three categories as active techniques, passive techniques or a combination of both [1]. Active techniques involve distortion of fluid flow using an external force such as magnetic fields [7] and pulsating flow [8]. In contrast, passive techniques require no external force and use solid particles [9], geometry modification [10] and vortex flow elements.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Bagherzadeh et al [16] investigated laminar flow using Reynolds numbers of 1, 10, and 50, and water/fluid nanofluid Al 2 O 3 with volumes of 0, 0.3, and 0.06 inside a small rectangular channel in order to enhance heat transfer under a homogeneous magnetic field with forces of H a = 0, 20, and 40. The results showed that in the case of a creep motion state, the narrow cross section caused by fluid flow could not be observed and that the increase in axial velocity was only due to the presence of an additional size of the micro-channel.…”
Section: Introductionmentioning
confidence: 99%